PENGARUH KOMPETENSI KERJA DAN KEMAMPUAN KOMUNIKASI TERHADAP KESIAPAN KERJA SISWA JURUSAN BISNIS RITEL DI SMK SWASTA TELADAN PEMATANGSIANTAR T.A 2025/2026 - Putri Elisabet Marpaung; Benjamin Albert Simamora; Eduward Situmorang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of work competency and communication skills on students' work readiness. This study used a quantitative approach with a causal associative method. The population consisted of 92 students, with a sample of 62 students selected using purposive sampling. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS version 25. The results showed that work competency had a positive and significant effect on work readiness, with a calculated t-value of 2.962, greater than the t-table value of 2.001, and a significance value of 0.004, less than 0.05. Communication skills had a positive and significant effect on work readiness, with a calculated t-value of 4.452, greater than the t-table value of 2.001, and a significance value of 0.000, less than 0.05. Simultaneously, work competency and communication skills had a significant effect on work readiness, with a calculated F-value of 56.384, greater than the F-table value of 3.153, and a significance value of 0.000, less than 0.05. The coefficient of determination value of 0.657 indicates that 65.7% of the variation in work readiness can be explained by the two variables. Communication skills have a more dominant influence than work competency.